Conditional Cash Transfers to Increase Retention in PMTCT Care, Antiretroviral Adherence, and Postpartum Virological Suppression: A Randomized Controlled Trial. (1st August 2016) - Yotebieng, Marcel; Thirumurthy, Harsha; Moracco, Kathryn E.; Edmonds, Andrew; Tabala, Martine; Kawende, Bienvenu; Wenzi, Landry K.; Okitolonda, Emile W.; Behets, Frieda
Abstract : Background: Novel strategies are needed to increase retention in prevention of mother-to-child HIV transmission (PMTCT) services. We have recently shown that small, incremental cash transfers conditional on attending clinic resulted in increased retention along the PMTCT cascade. However, whether women who receive incentives to attend clinic visits are as adherent to antiretrovirals (ARV) as those who do not was unknown. Objective: To determine whether HIV-infected women who received incentives to remain in care were as adherent to antiretroviral treatment and achieved the same level of viral suppression at 6 weeks postpartum as those who did not receive incentives but also remained in care. Methods: Newly diagnosed HIV-infected women at ⩽32 weeks gestational age were recruited at antenatal care clinics in Kinshasa, Democratic Republic of Congo. Women were randomized in a 1:1 ratio to an intervention or control group. The intervention group received compensation (5, plus 1 increment at each subsequent visit) conditional on attending scheduled clinic visits and accepting offered PMTCT services, whereas the control group received usual care. The proportion of participants who remained in care, were fully adherent (took all their pills at each visit) or with undetectable viral load at 6 weeks postpartum were compared across group. Results: Among 433 women randomized (216 in intervention group and 217 in control group), 332 (76.7%) remained in care at 6 weeks postpartum, including 174 (80.6%) in the intervention group and 158 (72.8%) in the control group, ( P = 0.04). Data on pill count were available for 297 participants (89.5%), including 156 (89.7%) and 141 (89.2%) in the intervention and control groups, respectively; 69.9% (109/156) and 68.1% (96/141) in the intervention and control groups had perfect adherence [risk difference, 0.02; 95% CI: −0.06 to 0.09]. Viral load results were available for 171 (98.3%) and 155 (98.7%) women in the intervention and control groups, respectively; 66.1% (113/171) in the intervention group and 69.7% (108/155) in the control group had an undetectable viral load (risk difference, −0.04; 95% CI: −0.14 to 0.07). Results were similar after adjusting for marital status, age, education, baseline CD4 count, viral load, gestational age, and initial ARV regimen. Conclusions: Although the provision of cash incentives to HIV-infected pregnant women led to higher retention in care at 6 weeks postpartum, among those retained in care, adherence to ARVs and virologic suppression did not differ by study group.